N-Acetylcysteine Prevents Sleep Deprivation-induced Memory Deficit in Juvenile Rats Through the Suppression of BDNF, Cortisol, Acetylcholine Levels, and Inflammatory Cytokines Expressions - Citra Rosyidah; Wawaimuli Arozal; Hee Jae Lee; Raymond Rubianto Tjandrawinata; Wahyunia Likhayati Septiana (The Prodia Education and Research Institute (PERI), 2025)
BACKGROUND: Sleep deprivation (SD) affects 20–30% of children and is known to impair cognitive functions, particularly memory. Despite its impact, there is currently no standardized treatment. Evidence from both adult animal and human suggests that N-acetylcysteine (NAC) possesses neuroprotective properties. This study was conducted to evaluate the effects of NAC on memory deficits induced by SD in juvenile rats.METHODS: Juvenile Sprague-Dawley rats were subjected to SD using the modified multiple platform method. NAC was administered intraperitoneally at doses of 100 mg/kgBW or 500 mg/kgBW. Y-maze and novel object recognition (NOR) tests were used for neurobehavioral assessment. Biochemical analyses were conducted to measure cortisol, brain-derived neurotrophic factor (BDNF), and acetylcholine (ACh) levels, using enzyme-linked immunosorbent assay (ELISA). Acetylcholine esterase (AChE) activity was measured by colorimetric method. Western blot analysis was performed to examine cAMP response element-binding protein (CREB) and phosphorylated CREB (p-CREB). Additionally, cytokine mRNA expressions were evaluated using polymerase chain reaction (PCR).RESULTS: Spontaneous alteration and discrimination ratio were decreased in SD group without treatment compared to the normal group (p<0.05). Similarly, BDNF was also decreased compared with normal group (p<0.05). Cortisol level and mRNA expression of TNF-α were increased significantly compared with normal group (p<0.05) along with a slight increase of ACh activity. Interestingly, NAC treatment mainly at the dose of 500 mg/kgBW prevented those pathological features significantly.CONCLUSION: NAC might prevent the SD-induced memory deficits by suppressing the inflammatory markers, activity of AChE, cortisol, and enhancing the level of BDNF.KEYWORDS: SD, NAC, memory, AChE, cortisol, inflammatory markers, BDNF